Drying Method of Pods for Extracting and Decreasing of Seed Moisture Content of Sengon Laut (Falcataria moluccana (Miq.) Barneby & J.W. Grimes - Muhammad Zanzibar (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2017)
The process of initial handling of seeds is extraction which is using dry or wet methods. The objective of this research was to find out the suitable pod drying period for extracting seeds and decreasing of seed moisture content of sengon laut. The experimental design used was a complete randomized design (CRD). The main factor was drying method under the sun and using seed drier (40°C). The results showed that either sun drying for 2 days or use seed drier for 32 hours was the best method for extraction and decreasing of seed moisture content. Drying pods was enable to obtain safe seed moisture content for long-term storage of Falcataria molucana seeds.